FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KAKAO DESA NGLANGGERAN KECAMATAN PATUK KABUPATEN GUNUNGKIDUL - Wahyu Adhi Saputro; Yuli Fidayani (JURNAL VIGOR, 2020)
Plantation is one of the agricultural sub sectors and one of these commodities is Cocoa. Cocoa is one of the export commodities from the plantation sub sector which is a national commodity.One area that develops and cultivates cocoa production is Nglanggeran, Patuk Subdistrict, Gunungkidul Regency. The purpose of this study was to analyze the factors that influence the production of cocoa beans in Nglanggeran Kecamatan Patuk Kabupaten Gunungkidul. The research method used a descriptive method of analysis by sampling the simple random sampling method. Type of data collected was primary data which was obtained by survey method using questionnaires. Data were analyzed with the Cobb Douglas functions. The results showed that factors which positively influenced on the increase of cocoa production were land area, use of pesticide and number of plants production. Meanwhile the amount of labor and the use of fertilizer had no significant effect on cocoa production